Microscopic colitis - state of current knowledge on pathogenesis, diagnostics and treatment - Bętkowska, Paulina; Licak, Gabriela; Olko, Paweł; Żuchnik, Magda; Rybkowska, Agnieszka; Tomkiewicz, Julia; Tomkiewicz, Michał; Radulski, Jakub; Sałata, Piotr; Paluch, Michał (Quality in Sport, 2023)
Introduction and purpose Microscopic colitis is multicausal inflammatory bowel disease, which affects mostly elderly, particularly women. It is a cause of chronic, watery diarrhea. MC usually presents macroscopically normal, thus diagnosis requires colonoscopy and histological examination of colonic biopsies. MC doesn’t increase risk of colon cancer. However, it leads to impaired patients’ quality of life and reduced living activity. This review aims to sum up the current state of knowledge about symptoms, diagnosis and treatment of microscopic colitis. Material and methods This review was based on available data collected in the PubMed database, using the following keywords: „microscopic colitis”, “microscopic colitis treatment”, „microscopic colitis pathogenesis”, and “ microscopic colitis diagnosis”. Conclusions Diagnosis of MC is often delayed due to similarity of clinical manifestation with other inflammatory bowel diseases, like IBS or IBD. Raising awareness about MC as a potential cause of chronic diarrhea can lead to earlier diagnosis and increased patients’ quality of life.